دراسة تحليلية لتأثير معايير المراجعة الدولية في الجزائر - عيدة أنور; هجريس سهيلة (جامعة الوادي University of Eloued, 2024)
سعت هذه الدراسة إلى تقييم واقع مهنة المراجعة في الجزائر، استكشاف الإجراءات العملية المتبعة في مهنة المراجعة بالبيئة الجزائرية وتحليل أوجه الشبه والاختلاف بين المعايير الجزائرية والدولية للمراجعة, تحقيقًا لهذه الأهداف تم الاعتماد على تحليل نتائج استبيان تم توزيعه على عينة من مراجعي الحسابات في الجزائر، كما أظهرت نتائج الدراسة أن معايير المراجعة الدولية حظيت بقبول واسع من قبل المختصين والمهتمين بمهنة المراجعة في الجزائر، حيث تساهم معايير المراجعة الدولية في تعزيز الثقة والمصداقية بالقوائم المالية للمستثمرين الأجانب. وبناءً على هذه النتائج، توصي الدراسة بضرورة عقد دورات تدريبية متخصصة لمراجعي الحسابات حول كيفية تطبيق معايير المراجعة الدولية. This study sought to evaluate the reality of the auditing profession in Algeria، explore the practical procedures followed in the auditing profession in the Algerian environment، and analyze the similarities and differences between Algerian and international auditing standards. To achieve these objectives، reliance was placed on analyzing the results of a questionnaire that was distributed to a sample of auditors in Algeria. The results of the study also showed that international auditing standards were widely accepted by specialists and those interested in the auditing profession in Algeria، as international auditing standards contribute to enhancing trust and credibility in auditing. Finance for foreign investors. Based on these results، the study recommends the need to hold specialized training courses for auditors on how to apply international auditing standards.
Analytical Study of the Impact of International Auditing Standards in Algeria: English Translation
Keywords: معايير المراجعة الدولية، مراجع الحسابات، المراجعة; مراجع الحسابات; المراجعة